2016
DOI: 10.11648/j.js.s.2016040201.15
|View full text |Cite
|
Sign up to set email alerts
|

Age - Related Gastric Changes

Abstract: Aging is a universal process with progressive loss of function accompanied by decreasing fertility and increasing mortality and disability. There are several mechanisms to underlie the primary aging process and probably contribute to agerelated changes in adaptive responses. These mechanisms are oxidative stress, mitochondrial theory, telomeres and cellular senescence, apoptosis and genetic mechanism. There are many physiological changes with aging process including blood pressure, temperature, fever, and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Both experimental and clinical studies had reported impairment in gastric mucosal defenses by aging as indicated by decrease in bicarbonate, mucus and PGs secretion, reduced NOS activity and reduced blood flow [22,33]. Moreover, Saber and Bayumi (2016) [34] indicated that elderly people have a decreased mucosal PGE2 concentration compared to adults. Our results also indicated that CIL increased gastric mucosal NO and PGE2 concentrations and gastric juice content of mucin in rats compared to adult and aged CRS groups.…”
Section: Discussionmentioning
confidence: 99%
“…Both experimental and clinical studies had reported impairment in gastric mucosal defenses by aging as indicated by decrease in bicarbonate, mucus and PGs secretion, reduced NOS activity and reduced blood flow [22,33]. Moreover, Saber and Bayumi (2016) [34] indicated that elderly people have a decreased mucosal PGE2 concentration compared to adults. Our results also indicated that CIL increased gastric mucosal NO and PGE2 concentrations and gastric juice content of mucin in rats compared to adult and aged CRS groups.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal or increased fiber intake is impossible for the group particularly at risk for cardiovascular diseases—elderly individuals, whose gastrointestinal issues necessitate a low-fiber diet. However, this type of diet exacerbates glycemic parameters and promotes the rapid absorption of lipids in the intestinal lumen [ 45 , 46 ].…”
Section: Food Compounds In Cardiometabolic Preventionmentioning
confidence: 99%